Prevalence and Risk Factors of Tinnitus Among University Students - Mahafza, Nadeem; Mahafza, Tareq; Mahafza, Marina; AlOmari, Hala (Jordan Medical Journal, 2023)
Objective: The purpose of this study was to investigate the prevalence of tinnitus and other associated risk factors among students from the University of Jordan. Methods and Design: This cross-sectional study included 1,302 students (785 females and 517 males; aged 17–30 years old) attending the University of Jordan. All participants completed a tinnitus survey that included questions concerning the presence of tinnitus and its characteristics, exposure to recreational noise, and smoking habits. Tinnitus discomfort was measured using an Arabic Visual Analogue Scale (VAS). Descriptive and inferential statistics were used to analyze the data. Results: The overall prevalence of tinnitus (continuous or intermittent) was 21.2% among participants, with females having 13.9% prevalence and males having 7.3%. Pearson’s Chi-square test revealed a significant association between tinnitus and the influence of the various risk factors (x2=102.09, df=4, p<0.001). In addition, tinnitus was more likely to be associated with noise exposure (29%) and smoking (15%), and less likely to be related to seasonal allergies and gender. The results of the VAS indicated that only 5% of the students reported that their tinnitus was extremely uncomfortable. Conclusion: According to the findings of this study, the prevalence of tinnitus among university students who participated in this study was 21.2%. Furthermore, our results showed that exposure to recreational noise and smoking were associated with the presence of tinnitus.